2022
DOI: 10.1021/acs.molpharmaceut.1c00648
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization Study of a Lipid Nanocapsule Formulation Intended for Drug Delivery Applications Using Small-Angle Scattering Techniques

Abstract: Lipid nanocapsules (LNCs) are increasingly being used for various drug delivery applications due to their versatile nature and ability to carry a wide variety of therapeutic drug molecules. In the present investigation, small-angle X-ray (SAXS) and neutron scattering (SANS) techniques were used to elucidate the structure of LNCs. Overall, size measurements obtained from SAXS and SANS techniques were complemented with dynamic light scattering, zeta potential, and cryogenic transmission electron microscopy measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[307] Small angle X-ray or neutron scattering (SAXS or SANS, respectively) are two other powerful techniques for understanding heterogeneities in nanotherapeutics' internal structure, e.g., the core diameter and shell thickness of lipid nanocapsules. [308,309] For a more comprehensive review of singleparticle analysis techniques we refer to the works of Yan et al [310] and Ramassamy et al [25] Enhanced insight into nanotherapeutic heterogeneity will also require more uniform and thorough reporting strategies. [311] For instance, DLS-based nanotherapeutic size measurements are conducted in diverse media, and the reporting manuscripts often do not specify if the number-, volume-, or intensity-based average is being disclosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[307] Small angle X-ray or neutron scattering (SAXS or SANS, respectively) are two other powerful techniques for understanding heterogeneities in nanotherapeutics' internal structure, e.g., the core diameter and shell thickness of lipid nanocapsules. [308,309] For a more comprehensive review of singleparticle analysis techniques we refer to the works of Yan et al [310] and Ramassamy et al [25] Enhanced insight into nanotherapeutic heterogeneity will also require more uniform and thorough reporting strategies. [311] For instance, DLS-based nanotherapeutic size measurements are conducted in diverse media, and the reporting manuscripts often do not specify if the number-, volume-, or intensity-based average is being disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 307 ] Small angle X‐ray or neutron scattering (SAXS or SANS, respectively) are two other powerful techniques for understanding heterogeneities in nanotherapeutics’ internal structure, e.g., the core diameter and shell thickness of lipid nanocapsules. [ 308,309 ] For a more comprehensive review of single‐particle analysis techniques we refer to the works of Yan et al. [ 310 ] and Ramassamy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nanocapsules are a newly developed lymphatic system nanodrug delivery carrier in recent years. Due to the controllable capsule size, distribution particle size, and good biocompatibility, they have been widely used in the development of lymphatic targeted drug delivery platforms for drug control release and antigen and adjuvant delivery [ 92 , 93 ]. Research found that small-sized (100 nm) polyamino acid nanocapsules have better lymphatic absorption and biological distribution characteristics.…”
Section: Lymphatic Diagnosis and Treatment Nanomedicinesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Phospholipids comprise bioactive agents, exerting a variety of therapeutic effects, as well as supramolecular-structure-forming materials, which interact with the biological barriers. [8][9][10] Lipid nanoparticles (LNPs), a class of nanometric drug delivery systems, have been successfully used in the development of anti-coronavirus vaccines and as reservoirs for the controlled delivery of various bioactive compounds. [11][12][13] In fact, encapsulating therapeutic molecules within LNPs helps enhance their bioavailability and stability, reducing the drug dose, and avoiding severe side effects.…”
Section: Introductionmentioning
confidence: 99%